Environmental Quality Cost Analysis at PT. Anugrah Harisma Barakah - Zalza Berlinda Pratiwi; Dian Anita Nuswantara (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study evaluates the environmental responsibility of the mining company PT. AHB in reducing the negative impacts of mining activities. The results show that PT. AHB has implemented programs to improve the environment in accordance with applicable government regulations. The company's environmental programs include: prevention costs (acid mine drainage mitigation, dam/pond construction, sampling), detection costs (laboratory analysis, procurement of monitoring equipment, water, air, and soil quality management, and environmental consultation), and internal failure costs (hazardous waste management, biodiversity, land management, nurseries, planting, and maintenance of flora/fauna). The company's environmental costs are also influenced by dynamic environmental conditions and often exceed the planned budget. As part of its business strategy, PT. AHB also integrates environmental costs into production costs. This study emphasizes the importance of the company's commitment to sustainable environmental management.